Fraud in academic medical research: lessons from Flanders, Belgium - De Winter, Jan; Kosolosky, Laszlo (The reasoner, 2013)
A scientific survey on fraud in academic medical research in Flanders , of which the results were recently published in popular science magazine Eos, has caused tumult in the Flemish academic community. The reason is that these results suggest that scientific fraud (which could indirectly cause ill health and death among patients) is not as rare as earlier estimates indicate . Malpractices are primarily attributed to the pressure to publish. In this piece , we elaborate on the content of the study and pave the way for reform.